Características dos sistemas precipitantes e ocorrências de relâmpagos no sudeste da Amazônia - MELO, Vanessa da Rosa (2019)
This paper used and analyzed 15 years of rainfall data and the occurrence of lightning provided by the Precipitation Radar (PR) and Lightning Imaging Sensor (LIS), which are sensors aboard the satellite Tropical Rainfall Measuring Mission (TRMM), observed over the tropical region and subtropical. Following the methodology of Nesbbit (2000), adapted by Mota (2003) from December 1997 to December 2012. As were used together, images of fire outbreaks during the years (2004 and 2005) provided by the National Institute of Space Research (INPE), for demonstrative effect of the presence of fire focuses on regions. An enclosed area, located between latitude 0 º S and 12 º S and longitude 58 ° W was used 46 ° W, data from each 1 x 1 and resized into a grid of 3 x 3, subdivided into 4 regions, between latitudes and longitudes , REG_1 (LAT 5 S 8 S and LON 53 º W 50 º), REG_2 (LAT 5 S 8 S and LON 50 º W 47 º W), REG_3 (LAT 8 ° S 11 ° S and 53 º W 50 º W) and REG_4 (LAT 8 ° S 11 ° S and LON 50 º W 47 º W). Covering parts of Pará, Mato Grosso and Tocantins. In order to observe the characteristics of precipitation systems in order to associate with the incidence or occurrence of lightning over the regions. The data sampled by TRMM satellite, which were identified as systems with all PFS and MCS are subdivided between systems (ALLPFS) systems unsigned ice (WOICE), systems with signature ice (WICE) and mesoscale convective systems (MCS). The study showed that the monthly variation of lightning on REG_3 and REG_4 are the most occurred, with the largest number of lightning, his monthly variation occurs in the months of OND and JFM, watching the rainy season in the region. And those who collaborated with the most precipitation systems were electrified MCSs.